The Flipped Learning Classroom Model and Graduate Students’ Cognitive Engagement in a Public University in Azerbaijan - Akter, Amrin (My University, 2026)
The Flipped Learning Classroom (FLC) model is internationally recognized for promoting active learning and thinking skills. This mixed-methods study examined the relationship between flipped learning readiness and graduate students’ cognitive engagement in the FLC model at a public university in the Republic of Azerbaijan using an explanatory sequential design. The adapted versions of Flipped Learning Readiness Scale (Hao, 2016) and Utrecht Work Engagement Scale (Schaufeli & Bakker, 2004) were completed by 72 graduate students in the quantitative phase. Flipped learning readiness and cognitive engagement are significantly positively correlated, with a correlation coefficient of r = .785 and p value < .001. Those students who took four or more FLC courses demonstrated significantly more cognitive engagement than students who took two or three (p = .044, Cohen’s d = 0.51). No significant difference was found by year of study. The qualitative phase identified six themes through semi-structured interviews with four purposefully selected students: FLC creates both engagement and burden; preparation determines participation; students develop coping strategies for the heavy workload; peer interaction enhances learning; students need clarity of focus; and material format influences motivation. The findings also included equity issues related to access to resources. This study contributes empirical evidence from the under-researched Azerbaijani context and demonstrates that prior FLC experience plays a key role in cognitive engagement. The findings offer practical guidance for instructors, program coordinators, and policymakers in implementing flipped learning in graduate education.
Keywords: Flipped Learning Classroom (FLC); Cognitive Engagement; Flipped Learning Readiness (FLR); Graduate Students; Higher Education; Mixed-Methods